Bioprospection of Some Plants for Management of Aedes egypti L. - Dinesh Vijigiri1, P. P. Sharma1*., A. B. Pardeshi2 and (Current Botany, 2011)
Insecticides and pesticides of plant origin have been receiving attention in recent years to overcome the environmental hazards caused due to exhaustive use of synthetic ones. India is rich in biodiversity and Known for vast treasure of knowledge about use of plants for various purposes. In the present study the different concentrations of ethanolic extracts of some plants were tested for larvicidal and adulticidal activity against the of Aedes ejypti L. The percentage mortality was found to increase with higher concentrations of plant extracts which indicates direct relationship between the dose and percent mortality. The plant Artemisia nilgirica (C.B.Cl.) Pamp. and Annona squamosa L. were shown wide spectrum activity to control vector Aedes ejypti L. While some other species such as Blumea eriantha DC. , Calotropis procera (Ait.) R. Br., Lavandula bipinnata O. Ktze. have also shown the activity.